Improved LEACH Routing Communication Protocol for a Wireless Sensor Network - Fuzhe Zhao; You Xu; Ru Li (International Journal of Distributed Sensor Networks)
A WSN (wireless sensor network) consists of thousands of sensor nodes with limited energy, memory, and computation capability. The applications of WSN in some extreme environment make sensor nodes difficult to replace once they use up the resource. Hence, many researchers in this field focus on how to design a property routing protocol to prolong the life span of the network. The classical hierarchical protocols such as LEACH and LEACH-C have better performance in saving the energy consumption. However, the choosing formula neglecting the change of Nodes' energy will make the nodes acting as cluster heads too many times die early owing to the consumption of too much energy. Also, the high frequency of reclustering wastes certain amount of energy. In order to make the energy distribute more evenly among different nodes, we improve the tradition equation used for selecting cluster heads with considering the dynamic change of nodes' energy. Meanwhile, we propose to establish a vice cluster head for each cluster during the communication process, which aims to diminish the energy consumption spent on the reclustering and prolong the time of being in a steady-state phase. Simulations show that our improved protocol performs better than the LEACH and the LEACH-C.